C-low threshold mechanoreceptor activation becomes sufficient to trigger affective pain in spinal cord-injured mice in association with increased respiratory rates - Noble, Donald J.; Dongmo, Rochinelle; Parvin, Shangrila; Martin, Karmarcha K.; Garraway, Sandra M. (Frontiers in Integrative Neuroscience, 2022)
The mechanisms of neuropathic pain after spinal cord injury (SCI) are not fully understood. In addition to the plasticity that occurs within the injured spinal cord, peripheral processes, such as hyperactivity of primary nociceptors, are critical to the expression of pain after SCI. In adult rats, truncal stimulation within the tuning range of C-low threshold mechanoreceptors (C-LTMRs) contributes to pain hypersensitivity and elevates respiratory rates (RRs) after SCI. This suggests that C-LTMRs, which normally encode pleasant, affiliative touch, undergo plasticity to transmit pain sensation following injury. Because tyrosine hydroxylase (TH) expression is a specific marker of C-LTMRs, in the periphery, here we used TH-Cre adult mice to investigate more specifically the involvement of C-LTMRs in at-level pain after thoracic contusion SCI. Using a modified light-dark chamber conditioned place aversion (CPA) paradigm, we assessed chamber preferences and transitions between chambers at baseline, and in response to mechanical and optogenetic stimulation of C-LTMRs. In parallel, at baseline and select post-surgical timepoints, mice underwent non-contact RR recordings and von Frey assessment of mechanical hypersensitivity. The results showed that SCI mice avoided the chamber associated with C-LTMR stimulation, an effect that was more pronounced with optical stimulation. They also displayed elevated RRs at rest and during CPA training sessions. Importantly, these changes were restricted to chronic post-surgery timepoints, when hindpaw mechanical hypersensitivity was also evident. Together, these results suggest that C-LTMR afferent plasticity, coexisting with potentially facilitatory changes in breathing, drives at-level affective pain following SCI in adult mice.